Traditional Sports and Games: Intercultural Dialog, Sustainability, and Empowerment - Saura, Soraia Chung; Zimmermann, Ana Cristina (Frontiers in Psychology, 2021)
From Traditional Sports and Games (TSG) we have not only learned different ways of living time as well as inhabit space and a particular mode of practicing sports and games from distinct cultures, but also promoting universal dialogue among people. TSG presents sustainable and ecological references for living needed even before the advent of the Covid-19 pandemic. Nowadays, environmentally friendly policies and production methods must be taken more seriously. TSG may reveal a path to sustainable development, considering our corporeality and cultural diversity. TSG are expressions of human groups that historically reproduce their way of life-based on modes of social cooperation and specific forms of relationship with nature, traditionally characterized by sustained environmental management. The purpose of this article is to discuss how TSG promotes intercultural dialogue with a focus on sustainability, and how it empowers people and creates equality among its players. We understand that TSG can break socio-cultural barriers. For this study, we considered data from a Brazilian experience of TSG’s Festival held at a public school in the city of São Paulo (Brazil), organized in collaboration with our study group. Data consists of observations registered in fieldwork during the processes of organization, preparation, implementation, and evaluation of a TSG Festival. The first step in our analysis is taken from a dynamic called “Talking Circles”, where researchers, registered dialogue about experiences and used specific literature about TSG, from a philosophical and anthropological perspective. What does this experience - from bodies in movement, artistic or sporting, or both - teach about intercultural dialogue and empowerment? Such gestures indicate a cultural heritage and corporeal wisdom that allows humans to face new encounters and understanding in peace, recognizing humanity common to all of us, regardless of our origins. Ethical and aesthetical results of such dialogue reveal possibilities to be explored in our relationship with different cultures and the environment, providing points of sustainable development through TSG.